Enterprise Factors Contributing to The Success of Malaysian Biotechnology SMEs: A Grounded Theory Approach - Bakar, Saridan Abu; Sulaiman, Mohamed; Osman, Intan (UI Scholars Hub, 2007)
While numerous empirical studies have been conducted in Western countries on biotechnology enterprises, little empirical research has been done in Malaysia especially in respect to the factors that contribute to the success of biotechnology small and medium enterprises (SMEs). In view of this, a study was undertaken recently in Malaysia to address this gap in the existing body of biotechnology knowledge. Using a grounded theory approach, this qualitative study managed to develop a conceptual framework that sheds useful information on the enterprise factors that significantly impact the success of Malaysian biotechnology SMEs. Specifically, this study found that organizational structure, innovation activities, linkages with academic research institutions, linkages with other private enterprises, personal linkages with academic researchers, access to financial capital, the procuring of government assistances, vertical integration, enterprise image, GMP compliance and halal certification, strongly influence enterprise success.